Steroid-induced dermatoses: a challenge for modern dermatology - H. I. Makurina; L. O. Cherneda (Zaporozhye State Medical University, 2024)
The aim of this work is to determine the variability and significance of motivating and provoking factors associated with the uncontrolled use of topical glucocorticosteroids, psychological features of this condition. Materials and methods. 50 patients with exacerbation of inflammatory dermatoses after long-term topical application of drugs with glucocorticosteroids as an active substance were examined. The key diagnostic measures were a clinical examination, an anamnesis collection with clarification of the activity class of the used agent, duration and potential reason for its systematic or periodic use. Assessment of the psycho-emotional state in relation to self-perception of one's own body was carried out using the dermatological version of the dysmorphic disorder questionnaire - BDDQ-DV. Results. The main pathology for which patients of both sexes used this group of drugs were rosacea, perioral dermatitis, and seborrheic dermatitis. Taking into account anamnestic data, the mean duration of application of topical corticosteroids in creams, ointments or lotions was 10.25 ± 3.50 months for women and 8.3 ± 1.6 months for the male cohort. Most patients received information about the need to use a topical steroid from acquaintances / friends and pharmacists. The most frequent pharmacological agent was betamethasone dipropionate. Analyzing the psychopathological aspect of the studied group, dysmorphic manifestations are prevalent and the most well argued. 32 individuals (64 %) from the cohort met the criteria for concern about the body or its parts. Conclusions. Regional clinical features of steroid-induced dermatoses, which are mostly represented by chronic inflammatory conditions located in aesthetically significant areas, have been determined. 64 % of patients with steroid-induced dermatoses develop a psychopathological profile. An important aspect remains the necessity to raise the awareness of medical, pharmaceutical workers, and the public about the need and correct use of topical corticosteroids.